A new species of the genus Paranthrenella Strand, 1916 (Lepidoptera: Sesiidae) from China - Yu, Tiantian; Gao, Lei; Kallies, Axel; Arita, Yutaka; Wang, Min (Zootaxa, 2021)
A new clearwing moth, Paranthrenella cinnamoma sp. nov., is described from southern China. Adults and genitalia are illustrated, DNA barcodes provided, and potential damage to Cinnamomum trees (Lauraceae) is described. Paranthrenella mushana (Matsumura, 1931) comb. nov. is transferred from Synanthedon Hübner, [1819]. A checklist of the species of Paranthrenella Strand, 1916 of China is provided.